Perceived Organizational Support and Self Efficacy on Employee Performance: The Mediating Role of Job Satisfaction at PDAM Tirta Hidayah Bengkulu City - Pratiwi, Okta Mustika; Nasution (Jurnal Manajemen, 2026)
In human resource development, employee performance in a company is essential to achieving corporate success. However, many companies face problems with low employee performance due to suboptimal human resource management, which hinders the achievement of corporate goals. This study aims to identify the influence of perceived organizational support and self-efficacy on employee performance, with job satisfaction as a mediating variable in employees at PDAM Tirta Hidayah Bengkulu City. This study uses a quantitative approach with data collection methods including questionnaires. The population in this study consists of all 361 employees of PDAM Kota Bengkulu. From this population, 183 people were selected using random sampling to be used as study data. In this case, the minimum sample size for the study was determined using Hair’s formula, which shows that the total sample can be calculated by multiplying the indicators by 5 or 10. There were 26 indicators in this study. Data analysis was performed statistically using the SmartPLS 3.0 data analysis software model. The results of the study show that perceived organizational support and self-efficacy significantly and positively affect employee performance, either directly or through job satisfaction. In addition, job satisfaction is a significant mediator in strengthening the impact of these two variables on employee performance.